Encouraging Students to Consider Music Education as a Future Profession. Issue 2 (February 2017) - Porter, Ann M.; Payne, Phillip D.; Burrack, Frederick W.; Fredrickson, William E.
The purpose of this study was to examine the attitudes, communication, and opportunities provided by music teachers to encourage consideration of the music teaching profession. Survey participants ( N = 436) were music educators from the Southeast (235), Midwest (51), and Southwest (149) National Association for Music Education regions of the United States. Fifty-two percent of respondents reported encouraging students to explore the music teaching profession, one third reported uncertainty about their encouragement of a music education career, and 21% indicated active discouragement. Personal job satisfaction, student music abilities, and constraints/forces outside the profession were factors for respondents who discourage students from the profession. A majority reported providing opportunities to explore the profession as a viable career option and those experiences reflected the authentic practices of the teaching profession. Professional development opportunities for in-service teachers in the encouragement of students toward music teaching should be strongly considered.